The Raison d'Être of Mutual Recognition: An Analysis of the 2015 Reform to Research Ethics Review Policies, Processes and Problems in Québec - Vasiliki Rahimzadeh (McMaster University Library Press, 2017)
Ethics review is a pre-requisite to conducting research involving humans in Canada, and indeed in most international jurisdictions. The Tri-Council Policy Statement on Ethical Conduct for Research Involving Humans (TCPS2) serves as the national policy framework for research ethics review in Canada, and outlines three potential oversight models: independent, delegated and reciprocal. While the independent model preserves institutional oversight of research, it contributes to a duplicative system that can unduly delay research and impose barriers to research collaboration. This analysis centres on a 2015 reform to the policy model of research ethics review for collaborative, multi-site studies in the province of Québec. Informal interviews with key informants supplemented a document analysis of provincial research ethics policies using the comparative framework proposed by Lavis and colleagues. Consolidating bureaucratic structures and preserving locally-relevant review studies that span multiple sites remain among the most pressing challenges to transitioning from an independent model, and could provide reference for other provinces that have, or are currently in the process of such a transition.